The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1038/aps.2012.50
|View full text |Cite
|
Sign up to set email alerts
|

Tissue cholesterol content alterations in streptozotocin-induced diabetic rats

Abstract: Aim: Diabetes is associated with elevated serum total cholesterol level and disrupted lipoprotein subfractions. The aim of this study was to examine alterations in the tissue cholesterol contents closely related to diabetic complications. Methods: Intraperitoneal injection of streptozotocin was used to induce type 1 diabetes in adult male Sprague-Dawley rats. On d 35 after the injection, liver, heart, intestine, kidney, pancreas, cerebral cortex and hippocampus were isolated from the rats. The content of total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 55 publications
3
13
1
Order By: Relevance
“…Finally we did not observe changes in cholesterol content in the diabetic heart which supports our conclusion that LXRs were not activated after injection of streptozotocin. Differences between our results and those obtained by Cheng et al [9] and Wang et al [25] might result from different duration of experiments (3-week study vs. 5 or 20-week study) and/or the type of animal model (Wistar rats vs. Sprague Dawley rats).…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…Finally we did not observe changes in cholesterol content in the diabetic heart which supports our conclusion that LXRs were not activated after injection of streptozotocin. Differences between our results and those obtained by Cheng et al [9] and Wang et al [25] might result from different duration of experiments (3-week study vs. 5 or 20-week study) and/or the type of animal model (Wistar rats vs. Sprague Dawley rats).…”
Section: Discussioncontrasting
confidence: 97%
“…Cheng et al [9] and Wang et al [25], found significant increase of ABCA1 and ABCG1 protein levels in the heart of diabetic rats. These transporters are responsible for cholesterol removal from cells [30], and they are under transcriptional regulation by LXRs [31].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A recent study by Wang et al has reported high-cholesterol levels in the STZ-induced rat brain with decreased expression of ApoE mRNA. However, they have observed decreased cholesterol levels and high ABCA1 expressions in peripheral tissues [273]. These results suggest that in case of diabetes, the body tends to decrease cholesterol levels by expressing ABAC1.…”
Section: Linking Lipids With Ad and Diabetesmentioning
confidence: 94%